The Executability of Capital Punishment under Indonesia’s 2023 Penal Code: A Legality Principle Analysis - Sari Mandiana; Go Lisanawati (KRTHA BHAYANGKARA, 2026)
The 2023 Indonesian Penal Code (KUHP Nasional) contains overlapping and inconsistent provisions regulating the execution of capital punishment, resulting in legal uncertainty at the level of implementation. This article examines the application of the death penalty under the KUHP Nasional from the perspective of the principle of legality, a fundamental pillar of criminal law requiring clarity and certainty in the formulation of criminal sanctions. Using a normative juridical approach, this conceptual study is based primarily on statutory analysis of the KUHP Nasional. The analysis demonstrates that the introduction of a mandatory probationary period for death sentences creates an internal contradiction within the Code, effectively rendering the execution of capital punishment legally impracticable, particularly following its full entry into force on 2 January 2026 as stipulated in Article 624. This article argues that the principle of legality must be understood not only in its formal dimension but also in its pragmatic dimension, especially at the judicial application stage. The main contribution of this study is its demonstration that the current legal construction of capital punishment in the KUHP Nasional undermines legal certainty and raises fundamental questions regarding the enforceability of the death penalty in Indonesia.